Por uma teorização das organizações de produção artesanal: habilidades produtivas nos caminhos singulares do Rio de Janeiro - Silva, Heliana Marinho da (2006)
The purpose of this thesis is to support the argument that workmanship production centers don¿t represent just survival strategy of social groups marginal to economical structure. Workmanship organizations are productive schemes that survived, in a parallel way, to the industrialization process, although they don¿t have been considered by the organization theory. The knowledge reserve in administration, from the traditional approach to critical studies, increased concerns on industrial organizations and business arrangements. Nevertheless, it is possible to find in Teoria da Delimitação dos Sistemas Sociais, from Guerreiro Ramos, elements to comprehend workmanship organizations as: technology, scale and sustainability, cognition, space and relationship and time. The research methodology used was bibliographic, field and documental, regarding action-research. It comes to the conclusion that, at present time, to keep it as distinct productive schemes, workmanship organizations must be associated to tourism and culture. The production must be thematic, with territorial identity, creative and sustainable, by the management of local raw material.